The Use of Social-networking Sites and Their Role in the Success of Women's Small-business Enterprises in Palestine - Herzallah, Ahmad Mohammad; Alnatsheh, Hanadi Mousa; Abd Alwahab, Yasmeen Mahmoud (Jordan Journal of Business Administration, 2025)
This study aims to identify the use of social-networking sites and their role in the success of small-business for women in Palestine. It adopts a descriptive-analytical method for the study design. To achieve the objectives of the study, a questionnaire (consisting of 38 items) was designed according to two variables. The first is the dependent variable, represented by small enterprises' success. The second variable is the independent variable, represented by using social networking sites. The study population consists of all small-business owners in Palestine, while convenience sampling is used to select (258) participants for data collection, in order to assess the study hypotheses using Square Structural-equation Modeling (SEM). The study findings show that the level of using social media to market small enterprises is high with a utilization rate of (81%). Further, the success level of small-business enterprises is high with a success rate of (79.8%). The study also reveals that the use of social media impacts the marketing of small enterprises. The length of time of the business and the business scope are seen as modifying variables for the impact of the use of social-media marketing on the success of small enterprises.